Perceptions of Team Members Working in Cleft Services in the United Kingdom: A Pilot Study. (January 2015) - Scott, Julia K.; Leary, Sam D.; Ness, Andy R.; Sandy, Jonathan R.; Persson, Martin; Kilpatrick, Nicky; Waylen, Andrea E.
Background: Cleft care provision in the United Kingdom has been centralized over the past 15 years to improve outcomes for children born with cleft lip and palate. However, to date, there have been no investigations to examine how well these multidisciplinary teams are performing. Methods: In this pilot study, a cross-sectional questionnaire surveyed members of all health care specialties working to provide cleft care in 11 services across the United Kingdom. Team members were asked to complete the Team Work Assessment (TWA) to investigate perceptions of team working in cleft services. The TWA comprises 55 items measuring seven constructs: team foundation, function, performance and skills, team climate and atmosphere, team leadership, and team identity; individual constructs were also aggregated to provide an overall TWA score. Items were measured using five-point Likert-type scales and were converted into percentage agreement for analysis. Results: Responses were received from members of every cleft team. Ninety-nine of 138 cleft team questionnaires (71.7%) were returned and analyzed. The median (interquartile range) percentage of maximum possible score across teams was 75.5% (70.8, 88.2) for the sum of all items. Team performance and team identity were viewed most positively, with 82.0% (75.0, 88.2) and 88.4% (82.2, 91.4), respectively. Team foundation and leadership were viewed least positively with 79.0% (72.6, 84.6) and 76.6% (70.6, 85.4), respectively. Conclusions: Cleft team members perceive that their teams work well, but there are variations in response according to construct.